Obliquely Deposited Gold Nanohelices on Lithography-Free Prepared Nanoseeded Surfaces - Yi-Jun Jen; Wei-Chih Liu; Chih-Yung Hsiao; Po-Cheng Lin; Chia-Liang Yu; Teh-Li Chan (Nanoscale Research Letters, 2017)
Abstract A substrate surface on which gold particles are distributed is prepared by annealing an ultra-thin gold film to enable glancing angle deposition. By cooling the substrate and controlling its spin rate, two spiral-like and one screw-like gold nanohelix arrays are grown upon the seeded surfaces. The mean helix radius and pitch length are reduced to 17 and 55 nm, respectively. The g-factor of the three nanohelix arrays is measured here and associated circular dichroism peak blue shifts occur as the gold helices shrink.